Evaluation of Online Learning Program during the Covid 19 Pandemic at SMKN I Koto XI Tarusan - Suci Andri; Ambiyar Ambiyar (STAI Miftahul Ula Nganjuk, 2021)
One of the problems related to the quality of online learning smk is the unpreparedness of vocational schools in the implementation of online learning. This study aims to evaluate online learning programs during the covid 19 pandemic at SMKN I Koto XI Tarusan as seen from inputs, activities (processes), outputs and outcomes. The research methods used are quantitative methods, instruments used questionnaires / questionnaires and data analysis techniques are carried out with quantitative methods, namely the dissemination of questionnaire stages: tabulating data, performing calculations of each score, calculating the total score, conducting descriptive analysis and percentage analysis. The subject of this study was a motorcycle business engineering student at SMKN I Koto XI Tarusan. Data collection techniques using questionnaires. The results showed that the implementation of online learning has been carried out obtained a percentage of 80.46% with a good category. The result of input components obtained a percentage of 79.83% with a sufficient category, components activities obtained a percentage of 79.83% with a sufficient category, component output obtained a percentage of 80.08% with a good category and component outcome obtained a percentage of 82.10% with a good category